In Silico Study of the YAKRCFR Peptide Structure and Its Interaction with Human Peroxiredoxin-5 - Jessika Maya Jovanka Najoan; Rymond Jusuf Rumampuk; Vlagia Indira Paat; Anderson Arnold Aloanis (Universitas Nusa Cendana, 2025)
The identification of bioactive peptides with therapeutic potential is an emerging focus in drug discovery. In this study, we evaluated the structural stability and binding affinity of the oyster-derived peptide YAKRCFR through molecular modeling and docking simulations against the human peroxiredoxin receptor. Structural prediction using the PEP-FOLD4 server revealed a consistent α-helical conformation across all models, stabilized by key intramolecular hydrogen bonds and favorable sOPEP energy values. Molecular docking was validated with a root mean square deviation (RMSD) of 0.273 Å, confirming the reliability of the docking protocol. The YAKRCFR peptide exhibited a strong binding affinity with the 1HD2 receptor (ΔG = –8.1 kcal/mol), outperforming both ascorbic acid (–6.1 kcal/mol) and the native ligand (–4.862 kcal/mol). Detailed interaction analysis indicated that YAKRCFR forms stable hydrogen bonds and van der Waals interactions with critical residues such as ILE A119 and PHE A120, contributing to its thermodynamic stability and binding specificity. These findings suggest that YAKRCFR holds promise as a lead compound for further development in peptide-based therapeutic strategies, particularly for targets involving the human peroxiredoxin receptor.